Increased vulvovaginal candidiasis incidence risk in various gestational ages at a private midwifery practice in Surabaya, Indonesia - Regina Martina Cilik; Willy Sandhika; Zakiyatul Faizah (Majalah Obstetri & Ginekologi, 2022)
HIGHLIGHTS 1. Hormonal changes during pregnancy lead to the presence of vulvovaginal candidiasis.2. Increased incidence of vulvovaginal candidiasis in different pregnancy trimesters were analyzed.3. Frequency of vulvovaginal candidiasis tends to increase along with the gestational age.   ABSTRACT Objectives: This study aimed to analyze whether there was an increase in the incidence risk of vulvovaginal candidiasis at various gestational ages. Materials and Methods: A study examined vaginal smears of pregnant women at a private midwifery practice Farida Hadjri, Surabaya, Indonesia. A total sample of 96 patients was taken by the consecutive sampling method, consisting of 32 patients each from the 1st, 2nd, and 3rd trimester of pregnancy.y The smear was examined using Gram stain at Balai Besar Laboratorium Kesehatan Daerah Jawa Timur to detect the presence of fungi elements. Data were analyzed using Chi-square test with 95% confidence interval to investigate whether there was an increased risk of vulvovaginal candidiasis and gestational age. Results: There was an increased risk of vulvovaginal candidiasis and increased gestational age (p < 0.05). This result was related to the hormonal status of pregnant women. An increase in estrogen level during pregnancy leads to an increase in glycogen production by vaginal epithelial cells, which cause the vaginal environment to become more susceptible to fungal growth. Conclusion: There was increased vulvovaginal candidiasis incidence risk along with gestational age. Pregnancy is one of the predisposing factors for candida infection.